Dissemination of Regional Legal Products "Socialization of Regional Regulation No. 10/2018 on the Protection and Empowerment of Local Traders at Hamadi Central Market, Jayapura City": Penyebarluasan Produk Hukum Daerah “Sosialisasi Perda No. 10 Tahun 2018 tentang Perlindungan dan Pemberdayaan Pedagang Lokal Di Pasar Sentral Hamadi Kota Jayapura” - Ohoiwutun, Yosephina Ohoiwutun; Agustinus, Agustinus Fatem; Ilham, Ilham (CONSEN: Indonesian Journal of Community Services and Engagement, 2024)
The implementation of this Community Service activity is entitled Dissemination of Regional Legal Products "Socialisation of Regional Regulation Number 10 of 2018 concerning Protection and Empowerment of Local Traders in Hamadi Market, Jayapura City". The method of implementing activities is carried out through observation and counselling. Furthermore, the socialisation of Regional Regulation Number 10 of 2018 concerning protection and empowerment for local traders or Indigenous Papuans is carried out in the hope that these regulations can be implemented and adhered to by the trader community. Through this socialisation, it is also expected that there will be no protests from non-indigenous Papuans regarding regulations that restrict them from selling local commodities, such as tubers, sago, vegetables, and local Papuan handicrafts such as woven noken. As a recommendation, the implementation of similar activities is expected to be carried out in other markets in Jayapura City.